(untitled) (Nigerian Journal of Physiological Sciences, 2021)
This study aimed at assessing the knowledge base and perception of telemedicine among veterinary students in Ghana. It involved a cross sectional survey and online structured questionnaires were administered to 114 veterinary students to access their knowledge of telemedicine and the perceived utilisation, benefits, complexity and disadvantages of telemedicine. Descriptive statistics analysis was performed on the data collected using SPSS version 20 and Pearson Chi-square test was used to determine the significant association between categorical variables which were grouped. Statistical significance was tested at 5% significance level. The students exhibited good knowledge and perception of telemedicine with a mean response of 4.947 ± 1.374 and 3.473±1.115; represented by 86.8% and 78.9% of the students respectively. 92.1% had heard of the term ‘telemedicine’ from the internet and social media platforms. The level of study of veterinary students had a significant effect (p<0.05) on their knowledge of telemedicine; knowledge increases with an increase in the year of study. Veterinary students showed good knowledge level and perception of telemedicine. However, exposure to the use of telemedicine system is low. Issues of patients’ information privacy being threatened by the usage of telemedicine were indicated. Development, incorporation of telemedicine in the curriculum in formative years of veterinary students training is critical to ensure effective and efficient training of students in telemedicine in the COVID era